Histological evaluation of platelet rich plasma and hydroxiapatite in apexogenesis: Study on experimental animals - Danilović Vesna; Petrović Vanja; Marković Dejan; Aleksić Zoran (Vojnosanitetski Pregled)
Background/Aim. There are very few data about the effects of endogenous growth factors in vital pulp therapy, and still they are often controversial. The aim of the study was to evaluate the effects of platelet rich plasma (PRP) in conjugation with hydroxyapatite (HAP), as pulp capping materials, to root and periodontium formation. Methods. Eight young monkeys (Cercopithecus Aethiops) with permanent dentition and incomplete root formation were involved in this study. After pulpotomy, the pulp lesion was capped with calcium hydroxide (control), hydroxyapatite (experimental group I) or hydroxyapatite in conjugation with PRP (experimental group II). Six months later, the animals were sacrificed, the tissue was removed en block, and prepared for the histological analysis in a routine way. Results. The results of the histological analysis revealed that healing process was characterised by dentin bridge formation, maintained morphological and functional integrity of dental pulp and complete formation of dental root and surrounding periodontium. The inflammatory reaction was scored as mild to moderate, in almost all the samples in all groups, suggesting the biocompatibility of the used materials. Conclusion. Materials used in this study are convenient as capping agents, contributing maintaining the integrity of the pulp tissue and facilitating root and periodontium formation. According to histological data it could be suggested that hydroxyapatite in conjugation with endogenous growth factors, represents superior alternative to other materials used in this study.